Do The Exploration Brioche, Savory Normandy Bread, Effective in Developing Appropriate Production and Marketing Strategies? - Ni Wayan Diah Satya Upayanti; I Nyoman Triana Putra; I Putu Adi Suantara; Ida Bagus Ade Pradnyana; Kadek Rian Permana; Ni Desak Made Santi Diwyarthi; Prastha Adyatma (Westscience Press, 2024)
This study conducts an in-depth exploration of brioche bread using qualitative research. A phenomenological approach with a research methodology based on depth interview and participant observation to reac the accurate data. The research findings reveal that Brioche bread's strengths lie in its delicious texture and taste, variety, and global marketing, while weaknesses include its relatively high price, limited shelf life, and unsuitability for daily needs. Opportunities for brioche bread include increasing nutritional awareness, new market expansion, and product innovation, while threats stem from intense competition, changing consumer preferences, and health regulations.